An Analysis of Vulnerable Languages of Bihar from Ecological Linguistic Perspective - Devina Krishna; Handoko Handoko (Jurnal Gramatika, 2024)
The emerging branch of linguistics known as ‘Ecolinguistics’ views language as an integral part of the ecological environment and aims to study the relationship between language and the environment. As an emerging discipline in linguistic research, ecolinguistics provides a new perspective on language research from an ecological point of view. The study of a language under the framework of ecolinguistics involves not only studying the language itself, but also the environment in which the language is located and the interrelationship between language and environment. The advantages of Hindi as the lingua franca in Bihar, one of the Indian states, have been highlighted, and people in many remote regions have switched to the powerful Hindi language, and many regional languages have become vulnerable. Bihar has been prone to multiple natural disasters which include flood, earthquake, drought, cyclonic storms, and lightening of high severity. For instance, 73.63% of the geographical area of North Bihar is prone to floods. Thus, these natural factors may wipe out a whole people leading to the creation of linguistic ecological crisis of their native languages. In addition to this, social factor also plays role wherein the spread and popularity of the Internet has strengthened the spread of Hindi as a common language in Bihar. Thus, the present paper studies the ecological languages of language vulnerability from the perspectives of ecolinguistics. The languages of Bihar such as ‘Angika’ and ‘Bajjika’ are facing the linguistic situation of vulnerability. Various factors lead to their present linguistic situation and therefore, the present paper attempts to study these languages from the ecological linguistic perspective. It also presents the strategies for preserving these ‘so-labelled’ vulnerable codes as the reduced linguistic diversity is as serious as the harm caused by reduced biodiversity.